A Uniform Approach to Contract Formation and Interpretation - McLauchlan, David (Victoria University of Wellington Law Review, 2025)
This is a revised and footnoted version of the Sir Ivor Richardson Lecture delivered at Victoria University of Wellington on 4 September 2024. Professor McLauchlan argues that when we ask the questions "is there a contract?" and, if so, "what does it mean?", essentially the same principles apply in New Zealand as a result of the Supreme Court's decision in Bathurst Resources Ltd v L&M Coal Holdings Ltd. This represents a departure from the law in other common law countries, notably the United Kingdom and Australia, where the courts continue to draw a sharp distinction between the principles governing formation of contracts and those governing their interpretation. Nevertheless, Professor McLauchlan suggests that the New Zealand development is to be welcomed because it improves the transparency and coherence of the law of contract and brings that law into line with the best international practice.